Great Mondays : how to design a company culture employees love - Levine, Josh (Brilliance Audio, 2019)
Building a workplace culture that maximizes employee engagement, performance, and retention for long-term business success Workplace culture is critical, and evidence suggests that it's a top driver of fiscal performance. Since 1998, organizations on Fortune's Best Companies to Work For list have outperformed the S & P index two-to-one and garnered nearly three times the cumulative stock market return. Great Mondays identifies the six key components of workplace culture, illustrating their connection to one another and explaining how they drive an organization's ability to find, keep, and support the best employees. The author provides an actionable framework for increasing retention, supporting employee engagement, and driving exceptional business performance, regardless of industry or business size. Implement the 6 components for creating a powerful culture -- Purpose, Values, Behaviors, Recognition, Rituals, and Cues --and launch your company to the top of your industry.